The Dark Hills Divide - Carman, Patrick (New York : Orchard Books, 2005)
When she finds the key to a secret passageway leading out of the walled city of Bridewell, twelve-year-old Alexa realizes her lifelong wish to explore the mysterious forests and mountains that lie beyond the wall.
Accelerated Reader AR